Historico da vacinacao antivariolica no Brasil - Telarolli R., Jr [UNESP] (My University, 1999)
A historical chronology of smallpox vaccination in Brazil is presented, with emphasis on the State of Sao Paulo. We also present the scientific and philosophical concepts that influenced the regulation and practice of vaccination in Sao Paulo based on the historiographic bibliography, legislation about vaccination, and the debates in the state legislative body. Discovered by Jenner in 1796, the vaccine reached in Brazil in 1804 and was only used in the colonial capital, the city of Rio de Janeiro. In the 1890 decade, smallpox, side by side with yellow fever, typhoid fever and other pestilential diseases, was the major health problem in the State of Sao Paulo. There was also the fear that the vaccine might transmit syphilis, an Unfounded attitude since the product used in Sao Paulo (the 'animal vaccine') was elaborated from bovine serum. The immediate necessity to fight a highly lethal disease that threatened the State population and the coffee-growing business led to the abandonment of the fears and of the liberal principles in favor of the sanitary needs. The vaccine became compulsory in 1891 in the State of Sao Paulo and its application met no resistance on the part of the population, in contrast to the so-called 'Vaccine Revolt' that would occur in Rio de Janeiro in 1904.
A survey of smallpox vaccination in Brazil
Keywords: History of medecine; History of medicine, 19th Century; Public health; Smallpox; Smallpox vaccine; bovine serum albumin; smallpox vaccine; Brazil; history of medicine; infection prevention; public health; vaccination